2005
DOI: 10.1007/s00404-004-0715-x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency peripartum hysterectomy in a tertiary London hospital

Abstract: Caesarean deliveries, especially repeat caesareans in women with placenta praevia, significantly increase the risk of emergency peripartum hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
62
3
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 10 publications
16
62
3
3
Order By: Relevance
“…In our series, 4 women (30.7%) developed disseminated intravascular coagulopathy, lower than the 33% rate previously reported by Smith and Mousa and Lau et al [17,22]. The febrile morbidity rate of 7.7% is lower than that of their studies [14,17,28]. There was one maternal death (7.7%) in our study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In our series, 4 women (30.7%) developed disseminated intravascular coagulopathy, lower than the 33% rate previously reported by Smith and Mousa and Lau et al [17,22]. The febrile morbidity rate of 7.7% is lower than that of their studies [14,17,28]. There was one maternal death (7.7%) in our study.…”
Section: Discussioncontrasting
confidence: 63%
“…Other factors that have been associated with EPH include advanced maternal age, multiparity, multiple gestations, and gestational diabetes. [2,[12][13][14][15][16] Conservative treatment of postpartum hemorrhage includes uterotonics (oxytocin, ergotamine), uterine massage, uterine artery embolization, uterine packing, pelvic vessel ligation, B-Lynch suture, multiple square sutures, and recombinant-activated factor VII [17]. The most severe complication of hemorrhage is maternal death, whose risk is estimated to be approximately 1 in 100,000 deliveries in developed countries and has been increasing.…”
mentioning
confidence: 99%
“…In UK, at tertiary care centre, there were 15 cases of emergency peripartum hysterectomy in 31,079 deliveries, giving the incidence of 0.48 per 1,000. Haemorrhage due to placenta praevia especially in repeat C section was the main indication for emergency peripartum hysterectomy (47 %) [7] while in Turkey at tertiary care centre, the incidence of emergency peripartum hysterectomy was 0.67 in 1,000 deliveries and hemorrhage due to uterine atony was the main indication for emergency hysterectomy (57.1 %). [8].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of emergency peripartum hysterectomy in this study did change significantly over the five year period giving an overall incidence of 3 per 1000 deliveries. This incidence is lower than the one reported from a study by Kwame-Aryee et al (2007) at Korle-Bu teaching hospital in Ghana, but higher than that reported in most studies elsewhere (Zamzami 2003;Okogbenin et al, 2003;El-Jallad et al, 2004;Selo-Ojeme et al, 2005;Katchy et al, 2006;Kwee et al, 2006;Yucel et al, 2006). The higher incidence of peripartum hysterectomy at Muhimbili may be due to the characteristic of the hospital being a referral institution, thus receiving cases which may need the procedure.…”
Section: Discussionmentioning
confidence: 52%